Shear Strength Reduction of Expansive Soil and Its Impact on Sheet Pile Structure Stability (Study at Cikarang District, Bekasi Regency, West Java) - Sudjatmiko, Eddy Triyanto; Alifia, Shilan Nazwa (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2025)
Expansive clay soils are classified as a problematic soil type, which is very sensitive to changes in moisture content. This sensitivity causes volume fluctuations and a decrease in soil strength parameters over time. The phenomenon has implications for the degradation of soil shear strength, which is often overlooked in long-term stability analysis. A real case happened in Bekasi Regency, where a slope retaining sheet pile experiencing a slant that was not predicted in the initial design. At the design and construction stage, the structure did not experience movement. However, over the time, the structure experienced a slow movement causing it to become lopsided and severely damaged, affecting the road below. This condition is suspected to be due to a decrease in soil strength over time. To investigate this issue, this thesis undertakes a numerical modeling approach with the Finite Element Method (PLAXIS 2D). It allows the simulation of gradual deterioration of soil parameters including cohesion (c), internal shear angle (ϕ) and modulus of elasticity (E) until results are obtained that match the current field conditions. The analysis revealed that the main cause of the sheet pile slope was a 35% decrease in soil shear strength after 13 years due to expansive soil characteristics. The cohesion of the top layer was reduced to 8.48 kN/m², the internal friction angle to 2.75°, and the elastic modulus to 1914.67 kN/m². In the second layer, the cohesion value was 25.14 kN/m², while the internal friction angle was 11.47° and the elastic modulus was 7218.71 kN/m². The cohesion in the third layer reached 36.28 kN/m², an internal friction angle of 12.71°, with an elastic modulus of 10466.96 kN/m², while in the fourth layer the cohesion reached 42.66 kN/m² and an internal friction angle of 13.42° with an elastic modulus of 12329.57 kN/m². Accompanied by a bending moment generated of 88.6 tons.m so it is recommended to use corrugated concrete sheet pile (CCSP) type W600 Type B for this condition. The study revealed that the stepwise decrease in the shear strength of the soil, caused by its expansive nature, was a major factor in the instability of the sheet pile structure.